REPRODUCTIVE CYCLE AND BIOCHEMICAL CHANGES IN THE GONADS OF THE FRESHWATER CRAB, BARYTELPHUSA CUNICULARIS (WESTWOOD, 1836) - Diwan, A D; Nagabhushanam, R (Indian Journal of Fisheries, 2011)
The annual breeding cycle of the crab, Barytelphusa cunicularis, was determined by measuring monthly the size of the gpnad relative to the size of the animal. The peak of gonad size appeared in rainy season (June to September) showing the maximum breeding activity during these months. Histological observations of the monthly gonads revealed that the ripening of the gonads started during March and extended upto May. By June the gonads of most of the individuals attained full maturity and spawning began. Spawning terminated by the end of September and the gonads entered a quiescent period. Monthly changes in the boichemical constituents of gonads were studied for one year to determine their variability in the course of the reproductive cycle. During the ripening of the gonads, glycogen, fat and protein contents were high. During spawning period all values fell considerably reaching the minimum values at the end of spawning season. During the maturation of the gonads glycogen, fat and protein contents were increased